2016
DOI: 10.1557/adv.2016.427
|View full text |Cite
|
Sign up to set email alerts
|

FTIR Ellipsometry Study on RF sputtered Permalloy-Oxide Thin Films

Abstract: The optical properties of RF sputtered polycrystalline permalloy oxide (PyO) thin films were studied in the infrared by variable angle ellipsometry. The dispersion of PyO shows a Lorentzian dispersion peak at 381.5 cm-1. We attribute this peak to the transverse optical phonon of PyO. This peak is consistent with a rocksalt crystal structure for the Ni0.81Fe0.19O1-δ thin films.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…With the sputtering vapor deposition technique, oxygen levels can be finely tuned to achieve near-stoichiometric or oxygen-poor AFM Ni 1−x Fe x O y thin films. Reports of dual ion beam sputtered Ni 1−x Fe x O (x = 0.19) and radio frequency magnetron sputtered Ni 1−x Fe x O confirm the rock salt crystal structure via X-ray diffraction for films sputtered at low oxygen pressure [34][35][36]. At lower concentrations, Wensheng et al have found, via X-ray diffraction, a rocksalt phase for pulsed laser deposition grown Ni 1−x Fe x O (x = 0.02), as well [37].…”
Section: Introductionmentioning
confidence: 99%
“…With the sputtering vapor deposition technique, oxygen levels can be finely tuned to achieve near-stoichiometric or oxygen-poor AFM Ni 1−x Fe x O y thin films. Reports of dual ion beam sputtered Ni 1−x Fe x O (x = 0.19) and radio frequency magnetron sputtered Ni 1−x Fe x O confirm the rock salt crystal structure via X-ray diffraction for films sputtered at low oxygen pressure [34][35][36]. At lower concentrations, Wensheng et al have found, via X-ray diffraction, a rocksalt phase for pulsed laser deposition grown Ni 1−x Fe x O (x = 0.02), as well [37].…”
Section: Introductionmentioning
confidence: 99%